Предподвижность в PRO-категории - Геворкян, П. С.
The notion of the premovability of the inverse spectrum in the procategory is defined and studied. The connection between movability o f the inverse spectrum and A-movability of topological space is established. The some well-known results in the shape theory are established as a corollary.
Keywords: Математика